2018
DOI: 10.5502/ijw.v8i2.734
|View full text |Cite
|
Sign up to set email alerts
|

Scaling the heights of positive psychology: A systematic review of measurement scales

Abstract: The volume of empirical research on positive psychology topics has grown substantially over the past two decades. This review examines how constructs in positive psychology have been operationalized, measured, validated, cited, and applied to build the science. Based on an archive of 972 empirical articles linked to positive psychology, this review found that 762 articles used at least one measurement scale; 312 measures were created or adapted. Findings reveal a wide range of scales being used to measure a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 36 publications
(42 reference statements)
3
19
0
Order By: Relevance
“…Due to its broad trans-philosophical, cross-cultural and diachronic perspectives, the VIA framework is meant to be a universally applicable individual differences model (Dahlsgaard et al, 2005). It is therefore not surprising that the framework has received roughly 10,000 citations at the time of this writing (Ackerman et al, 2018).…”
Section: Relevance Of the Via Character Frameworkmentioning
confidence: 99%
“…Due to its broad trans-philosophical, cross-cultural and diachronic perspectives, the VIA framework is meant to be a universally applicable individual differences model (Dahlsgaard et al, 2005). It is therefore not surprising that the framework has received roughly 10,000 citations at the time of this writing (Ackerman et al, 2018).…”
Section: Relevance Of the Via Character Frameworkmentioning
confidence: 99%
“…The majority of those were from the United States, where the movement linked to this approach originated. In the same direction, Ackerman, Warren and Donaldson (2018) demonstrated that the set of empirical researches on the topics of Positive Psychology evolved in a significant manner around the world in the last two decades. Based on an archive of almost a thousand empirical articles linked to the field, the review stated that 762 articles utilized at least one scale of measurement and that 312 measures were created or adapted, which shows the close relationship between Psychological Evaluation and Positive Psychology.…”
Section: Resultsmentioning
confidence: 95%
“…Finally, it can be considered that Positive Psychology is a growing approach in the Brazilian context, however, when compared to the international scenario, it seems to be little utilized (Kim et al, 2018). Scholars of Positive Psychology have been presenting important progress around the world while emphasizing human virtues in the name of well-being (Ackerman et al, 2018). Therefore, it is hoped that studies and interventions in this approach can be not only prosperous in the psychological sciences, but can also be beneficial to different contexts and fields.…”
Section: Final Considerationsmentioning
confidence: 99%
“…There are many measures of wellbeing ( Ackerman et al, 2018 ), tapping into outcomes ranging from finding meaning in one’s life to mindful awareness to one’s sense of community support. Our approach was to use a wide range of accepted measures of adult wellbeing, and reduce the measures to a manageable set using exploratory and confirmatory factor analyses, and then examine how the resulting factors align with the three hypothesized outcome clusters.…”
Section: Methodsmentioning
confidence: 99%
“…The Satisfaction with Life Scale (SWL) ( Diener et al, 1985 ), one of the most commonly used measures of wellbeing ( Ackerman et al, 2018 ), consists of five items (e.g., “In most ways my life is close to my ideal”; α = 0.87) which participants rate using the same 7-point scale ranging from strongly disagree to strongly agree . Ratings for each of the five items are summed up to calculate a single aggregate score.…”
Section: Methodsmentioning
confidence: 99%